ChemInform Abstract: Divergent Total Syntheses of (‐)‐Lycopladine D, (+)‐Fawcetttidine, and (+)‐Lycoposerramine Q. Issue 14 (8th April 2014) - Zeng, Chen; Zheng, Changwu; Zhao, Jingyun; Zhao, Gang
Abstract Enantioselective total syntheses of (+)‐fawcettidine (I) and (+)‐lycoposerramine Q (II) as well as the first total synthesis of (‐)‐lycopladine D (III) from a common intermediate is accomplished by a divergent path (not shown).